ФАНЛАРАРО ИНТЕГРАЦИЯ ОРҚАЛИ ТЕХНИКА ОЛИЙ ТАЪЛИМ МУАССАСАЛАРИДА БЎЛАЖАК КАСБ ТАЪЛИМИ ЎҚИТУВЧИЛАРИ КАСБИЙ КОМПЕТЕНТЛИГИНИ ШАКЛЛАНТИРИШ - Химматалиев, Д.О. (SCIENCE and SOCIETY, 2017)
The article is devoted to one of the most pressing challenges facing higher education today - the formation of professional competence of university students. The competitiveness of the labor market demands of today's students meet modern requirements of economic development, and subsequently formed the competence ensure readiness of students for their professional activities. Therefore, the authors believe that the professional competence of students of technical colleges can begin to form in the first stage of training through the context of learning and interdisciplinary integration, since contextual training constructed professional skills of students to carry out engineering activities, including many aspects, and interdisciplinary communication, in turn, It combines their knowledge and skills from different disciplines, directs the final result - the professional competence. Formed quality will help future technicians holistically apply knowledge of different fields of science in their professional engineering and be competitive specialists in the conditions of modernization of modern enterprises.
Keywords: qualification; competence; techical education; interdiscilinary integration; professional education; cycle of subjects